Neuroplasticity at Home: Improving Home-Based Motor Learning Through Technological Solutions. A Review - Forman, Christian Riis; Nielsen, Jens Bo; Lorentzen, Jakob (Frontiers in Rehabilitation Sciences, 2021)
Background: Effective science-based motor rehabilitation requires high volume of individualized, intense physical training, which can be difficult to achieve exclusively through physical 1-on-1 sessions with a therapist. Home-based training, enhanced by technological solutions, could be a tool to help facilitate the important factors for neuroplastic motor improvements. Objectives: This review aimed to discover how the inclusion of modern information and communications technology in home-based training programmes can promote key neuroplastic factors associated with motor learning in neurological disabilities and identify which challenges are still needed to overcome. Methods: We conducted a thorough literature search on technological home-based training solutions and categorized the different fundamental approaches that were used. We then analysed how these approaches can be used to promote certain key factors of neuroplasticity and which challenges still need to be solved or require external personalised input from a therapist. Conclusions: The technological approaches to home-based training were divided into three categories: sensory stimuli training, digital exchange of information training, and telerehabilitation. Generally, some technologies could be characterized as easily applicable, which gave the opportunity to promote flexible scheduling and a larger overall training volume, but limited options for individualized variation and progression. Other technologies included individualization options through personalized feedback that might increase the training effect, but also increases the workload of the therapist. Further development of easily applicable and intelligent solutions, which can return precise feedback and individualized training suggestions, is needed to fully realize the potential of home-based training in motor learning activities.